Development of a primary reference material of natural C-reactive protein: verification of its natural pentameric structure and certification by two isotope dilution mass spectrometry. Issue 5 (22nd January 2021) - Liu, Jianyi; Zhu, Wen; Sun, Haofeng; Song, Dewei; Xiao, Peng; Xu, Bei; Li, Hongmei
Abstract : Development of a primary reference material of natural C-reactive protein: verification of its natural pentameric structure and certification by two isotope dilution mass spectrometry. Abstract : C-reactive protein (CRP) is one of the most commonly used biomarkers for inflammation. The standardisation of a procedure for the detection of CRP has attracted significant attention globally, and primary reference materials of CRP based on the recombinant expression of E. coli that exist in the form of monomers have been developed. However, a primary reference material of natural CRP is still required to achieve the exact matching of CRP measurements in secondary reference materials ( e.g. CRP in frozen human serum). Herein, the development process for a certified reference material of natural CRP is reported, namely GBW09228. The raw material employed in this study was CRP extracted and purified from human body fluid, and exhibits a natural and verified pentameric structure. Through the use of amino acid analysis isotope dilution mass spectrometry (AAA-IDMS) and signature peptide-IDMS, this reference material was certified, and its certification results can be traced to SI units. The developed method was evaluated for its accuracy using the international comparison tests of the National Metrology Institute of Japan (NMIJ) and the Korea Research Institute of Standards and Science (KRISS). Overall, a CRP primary certified reference material (CRM) of well-characterised purity was determined that could be used to calibrate an IDMS-based reference method, that could then be used to assign target values to secondary CRMs. These secondary CRMs could in turn be used to calibrate and verify the accuracy of immunoassays, thereby giving a good foundation for establishing a complete traceability chain for CRP.